2015
DOI: 10.4103/0976-237x.152931
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between maxillary rotation and nasal morphology in males

Abstract: Background:Nasal features are important in treatment planning for orthodontic treatment.Aims and Objectives:The purpose of the study was to assess the relationship between maxillary inclination and nasal morphology in males.Materials and Methods:Forty-five samples were selected for the study between the age group of 18 and 30 years. Selected individuals were subjected to cephalometric radiography. These lateral cephalograms were traced and divided into three groups on the basis of the angle given by Schwarz fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Three studies 28, 29, 34 showed a negative correlation of the angle of inclination (AOI) with nasal length and nasal depth, while 2 studies 28, 34 showed a significant positive correlation of AOI with UNLA, thus suggesting the presence of an upturned nose in an anticlockwise-rotated maxilla. AOI was found to be negatively correlated with NTA by 2 studies, 29, 31 while a positive correlation was seen in 2 other studies. 28, 34…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Three studies 28, 29, 34 showed a negative correlation of the angle of inclination (AOI) with nasal length and nasal depth, while 2 studies 28, 34 showed a significant positive correlation of AOI with UNLA, thus suggesting the presence of an upturned nose in an anticlockwise-rotated maxilla. AOI was found to be negatively correlated with NTA by 2 studies, 29, 31 while a positive correlation was seen in 2 other studies. 28, 34…”
Section: Discussionmentioning
confidence: 82%
“…Two studies 24, 25 included only males in the sample, while 2 studies 23, 26 included only females, out of which one of the studies 26 was conducted on White adolescent females only. One study 31 included only adult males with skeletal class I molar relation on both sides. In 2 studies, 22, 25 only class I and class II samples were analyzed and no class III subject was present.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations